Transcultural Adaptation and Psychometric Support for a Brazilian Portuguese Version of the Flow State Scale (FSS-2). Issue 3 (June 2022) - Garcia, William F.; Nascimento Junior, José Roberto A.; Mizoguchi, Marcus V.; Brandão, Maria R. F.; Fiorese, Lenamar
The flow experience in sports is a construct of great interest to recreational and competitive athletes, coaches, and psychologists in pursuit of optimal performance. As there are no validated instruments for evaluating flow in the Brazilian Portuguese language, we evaluated the psychometric properties of a Brazilian version of the Flow State Scale (FSS-2) through three steps. Initially, four translators and five sports psychology specialists adapted the FSS-2 content for the Brazilian Portuguese language. Second, 371 athletes of both sexes who were engaged in group and individual sport modalities and who participated in national university sports competitions from 24 states responded to the adapted version of the FSS-2. Third, an independent sample of 34 athletes from Paraná responded to both the adapted FSS-2 and the dispositional flow scale (DFS-2) to permit analysis of the external validity and temporal stability of the adapted FSS-2. We found that the Brazilian version of the FSS-2 contains clear and pertinent items with a good content validity coefficient (CVC = 0.94) and satisfactory internal consistency (α > 0.88/CC > 0.80). Confirmatory factor analysis revealed that the adapted 36-item model presented adequate fit [X 2 (558) = 1258.85; X 2 /df = 2.256; comparative fit index (CFI) = 0.92; non-normed fit index (NNFI) = 0.90; Tucker–Lewis Index (TLI) = 0.91; root mean square error of approximation (RMSEA) = 0.06 (0.05–0.06); (RMSEA <0.05) =. 001] with all first order factors (challenge-skills balance, action-attention fusion, clear goals, feedback, intense concentration, control, loss of self-awareness, time transformation, and autotelic experience). External validity (r > 0.344) and temporal stability (0.53 < intraclass correlation coefficient (ICC) < 0.86) were satisfactory. We conclude that the Brazilian version of FSS-2 is adequate to evaluate flow states experienced by Brazilian athletes following a sports competition.